2006
DOI: 10.1007/s11625-006-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated and comprehensive estimation of greenhouse gas emissions from land systems

Abstract: Exchanges of carbon and nitrogen between the atmosphere and terrestrial ecosystems involve a complex set of interactions affected by both natural and management processes. Understanding these processes is important for managing ecosystem productivity and sustainability. Management processes also affect the net outcome of exchanges of greenhouse gases between terrestrial ecosystems and the atmosphere. In developing a national carbon accounting system (NCAS) for Australia to account for emissions and removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…For example, Brack et al (2006) found good agreement between the modelled and observed aboveground biomass (from ages 10-14) and volume (ages 10-29) data for a P. radiata research site in the Australian Capital Territory. England et al (2006) demonstrated excellent agreement between FullCAM outputs and aboveground biomass estimates obtained from destructive sampling of Eucalypt farm forestry plantations aged between 5 and 12 years in south east Australia (r 2 = 0.92, n = 7), England et al (2006) also found good results for natural and tubestock environmental plantings (r 2 = 0.70, n = 7; r 2 = 0.75, n = 7, respectively), although results from direct seeded plantings of low aboveground biomass (<20 t/ha) were less encouraging (r 2 = 0.16, n = 7).…”
Section: Model Validation and Testing Programsmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, Brack et al (2006) found good agreement between the modelled and observed aboveground biomass (from ages 10-14) and volume (ages 10-29) data for a P. radiata research site in the Australian Capital Territory. England et al (2006) demonstrated excellent agreement between FullCAM outputs and aboveground biomass estimates obtained from destructive sampling of Eucalypt farm forestry plantations aged between 5 and 12 years in south east Australia (r 2 = 0.92, n = 7), England et al (2006) also found good results for natural and tubestock environmental plantings (r 2 = 0.70, n = 7; r 2 = 0.75, n = 7, respectively), although results from direct seeded plantings of low aboveground biomass (<20 t/ha) were less encouraging (r 2 = 0.16, n = 7).…”
Section: Model Validation and Testing Programsmentioning
confidence: 83%
“…Enhancing the FullCAM system to allow its application in plantation systems required: a method for calibrating the generalised growth model used by FullCAM for use in plantations; the ability to include the effects of management on growth at any point in a rotation; a knowledge of past management practices and their effects on growth; understanding of the pattern of development of Australia's plantation estate. A full description of FullCAM, its other component models, the calibration and verification methods used, and related data sources are outlined in Brack et al (2006). Kesteven et al (2004) describe the Forest Productivity Index (FPI), a continental site index developed for Australia's National Carbon Accounting System (NCAS).…”
Section: Model Developmentmentioning
confidence: 99%
“…High aerosol levels, resulting principally from recent volcanic activity, have thus protected Caribbean reefs from more frequent widespread bleaching events but cannot be relied on to provide similar protection in the future. Brack et al (2006) developed a comprehensive model for estimating GHG emissions from land systems in Australia. The model includes the effects of climate, land cover change, crop yield, and forest growth.…”
Section: Climatementioning
confidence: 99%
“…Scenario development to assess whether this cycling might change as a result of forest alteration (e.g. degradation induced by climate change) is also needed and is becoming increasingly important as a research field (Brack et al 2006;Lucas et al 2008). A better knowledge of forest ecosystems is critical to greenhouse gas control and biodiversity conservation.…”
Section: Introductionmentioning
confidence: 99%